Machiavelli Meets Michelangelo: Newspaper Coverage of the Arts in Singapore. (20th April 2016) - Freeman, Bradley C.; Duffy, Andrew J.; Xu, Xiaoge
This article examines newspaper coverage of the arts in Singapore to consider the role of the island state's newspapers in the development and documentation of Singapore's growing arts scene. Sampling two constructed weeks for each of 10 years, 1999 to 2008, content analysis is used to examine arts coverage in the Straits Times and Lianhe Zaobao . The study benefits from groundwork laid by Janssen's 1999 study of arts coverage in Dutch newspapers, in which not only quantity of content was reported but also hierarchical attention was paid to art forms over decades. Singapore is of interest as it represents a country where neither the arts nor newspapers are declining, and both enjoy significant overseeing by the government.